Neighborhood ethnic diversity and trust: the role of intergroup contact and perceived threat. - Schmid, K; Al Ramiah, A; Hewstone, M (2014)
This research reported here speaks to a contentious debate concerning the potential negative consequences of diversity for trust. We tested the relationship between neighborhood diversity and out-group, in-group, and neighborhood trust, taking into consideration previously untested indirect effects via intergroup contact and perceived intergroup threat. A large-scale national survey in England sampled White British majority (N = 868) and ethnic minority (N = 798) respondents from neighborhoods of varying degrees of diversity. Multilevel path analyses showed some negative direct effects of diversity for the majority group but also confirmed predictions that diversity was associated indirectly with increased trust via positive contact and lower threat. These indirect effects had positive implications for total effects of diversity, cancelling out most negative direct effects. Our findings have relevance for a growing body of research seeking to disentangle effects of diversity on trust that has so far largely ignored the key role of intergroup contact.